Manajemen Sarana dan Prasarana di MTs Bakti Satria - Ira Hamidatul Apiah; Asri Nurwardah; Ahmad Farihin; Pipinya Avina Fathanah (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2023)
Facilities and infrastructure play a crucial role in facilitating and enhancing the learning process. The purpose of this study is to provide a description of: (1) what is the history of MTs Globally MTs Bakti Satria, (2) what is the profile of MTs Bakti Satria, (3) what is the status of land ownership for the MTs Bakti satria school, (4) using alternatives or what method the acquisition process of facilities and infrastructure in MTs Bakti Satria, (5) whether every purchase and procurement of facilities and infrastructure is planned, (6) Who is involved in preparing school facilities and infrastructure planning, (7) What is the role of the collective effort of all school members in maintaining school facilities and infrastructure (8) Is aligning each room with its designated function. For this study, a qualitative approach was employed, which encompassed data collection through interviews, observations, and documentation. To analyze the data, qualitative analysis techniques were employed, encompassing data processing, data presentation, and drawing initial conclusions. The findings of this study reveal that: (1) Madrasah Tsanawiyah Bakti Satria was established in 1985. The establishment of this Madrasah was primarily motivated by a fundamental problem that was quite straightforward. (2) MTs Baki Satria was founded in 1985 by the founder, Mr. KH. Ali Shodiqin Akhyar. (3) About 5 hectares of land ownership comes from the waqf of Mr. H. Ahyar, the parents of Mr. KH. Ali Shodiqin Akhyar. (4) Meanwhile, the community self-supporting physical assistance (procurement of the madrasah tsanawiyah building comes from the proceeds from the acquisition of waqf fields and is added to the costs of the community. (5) MTs Bakti Satria ideally should be planned in advance regarding the procurement of school facilities and infrastructure. (6) ) Chairman of the Islamic education foundation Darul Akhyar, madrasah committee, head of madrasah (7) The role of residents in maintaining facilities and infrastructure only involves alumni who are specialized in the field of cleanliness so we use their services.(8) The condition of the classrooms is adequate but not yet perfect means that the class size is not standard because the initial target has not been achieved.